2017
DOI: 10.1101/134270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cell culture platform forcryptosporidiumthat enables long-term cultivation and new tools for the systematic investigation of its biology

Abstract: Cryptosporidium parasites are a major cause of diarrhoea that pose a particular threat to children in developing areas and immunocompromised individuals. Curative therapies and vaccines are lacking. Currently, Cryptosporidium oocysts for research must be freshly produced in animals and cannot be long-term stored. Here, we show that COLO-680N cells infected with two different Cryptosporidium parvum strains (Moredun, Iowa) produce sufficient infectious oocysts to infect subsequent cultures. Oocyst identity was c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Previous studies recently demonstrated the successful long-term propagation of C. parvum in COLO-680N cell culture [22]. The ability of the cell culture to maintain the parasite for up to 8 weeks [22,23] along with the presence of organelles around the parasite (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies recently demonstrated the successful long-term propagation of C. parvum in COLO-680N cell culture [22]. The ability of the cell culture to maintain the parasite for up to 8 weeks [22,23] along with the presence of organelles around the parasite (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We validated our methodology by comparing faecal profile results to the previously published studies, which used different methodologies, namely GC-MS [27,28]. Further experimentation utilised a recently published infectible culture, COLO-680N [22], to determine if any similarities or differences in response to infection could be determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…have mutualistic, commensalistic, and parasitic effects on this host (Table S1). A long-term goal would be the development of an in vitro and axenic (animal-and tissue-free) culturing system [63,64] that would further permit the exploration of the basic cell and developmental biology of gregarines. Despite their importance, research on gregarines is progressing very slowly, and it will require researchers from various disciplines to come together and provide their expertise in expanding our knowledge on the evolution of parasitism in these microbes.…”
Section: Discussionmentioning
confidence: 99%
“…The debate about the relationship between Cryptosporidium and the gregarines has not been settled yet, and the current phylogenetic placement of the Cryptosporidia has two important implications: (i) parasitism of vertebrates in the apicomplexans might have evolved twice (Figure 1), and (ii) if this proves to be true, Cryptosporidium could be used as a model system to elucidate the biology of gregarines. There have been rapid advancements in the methodological approaches [3] for the study of the parasites, including the development of an in vitro cell culturing system in cell lines [63] and organoids [70,71] along with the development of genetic tools such as CRISPR/Cas9 [72] and small interfering RNA (siRNA) [73]. In addition, there are several 'omics' methods that have been introduced including in vitro transcriptomics [74,75], proteomics [63,76], metabolomics [60], and state-of-the art microscopy techniques [63], including immunomicroscopy [63,77], to understand the invasion strategies and host-parasite interactions.…”
Section: Gregarines Can Elevate Our Understanding Of Parasitism and Imentioning
confidence: 99%